Optimization of calcium carbonate precipitation during alpha-amylase enzyme-induced calcite precipitation (EICP) - Albenayyan, Norah; Murtaza, Mobeen; Alarifi, Sulaiman A.; Kamal, Muhammad Shahzad; Humam, Abdulmohsen; AlAhmari, Manar M.; Khalil, Amjad; Mahmoud, Mohamed (Frontiers in Bioengineering and Biotechnology, 2023)
The sand production during oil and gas extraction poses a severe challenge to the oil and gas companies as it causes erosion of pipelines and valves, damages the pumps, and ultimately decreases production. There are several solutions implemented to contain sand production including chemical and mechanical means. In recent times, extensive work has been done in geotechnical engineering on the application of enzyme-induced calcite precipitation (EICP) techniques for consolidating and increasing the shear strength of sandy soil. In this technique, calcite is precipitated in the loose sand through enzymatic activity to provide stiffness and strength to the loose sand. In this research, we investigated the process of EICP using a new enzyme named alpha-amylase. Different parameters were investigated to get the maximum calcite precipitation. The investigated parameters include enzyme concentration, enzyme volume, calcium chloride (CaCl2) concentration, temperature, the synergistic impact of magnesium chloride (MgCl2) and CaCl2, Xanthan Gum, and solution pH. The generated precipitate characteristics were evaluated using a variety of methods, including Thermogravimetric analysis (TGA), Fourier-transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD). It was observed that the pH, temperature, and concentrations of salts significantly impact the precipitation. The precipitation was observed to be enzyme concentration-dependent and increase with an increase in enzyme concentration as long as a high salt concentration was available. Adding more volume of enzyme brought a slight change in precipitation% due to excessive enzymes with little or no substrate available. The optimum precipitation (87%) was yielded at 12 pH and with 2.5 g/l of Xanthan Gum as a stabilizer at a temperature of 75 °C. The synergistic effect of both CaCl2 and MgCl2 yielded the highest CaCO3 precipitation (32.2%) at (0.6:0.4) molar ratio. The findings of this research exhibited the significant advantages and insights of alpha-amylase enzyme in EICP, enabling further investigation of two precipitation mechanisms (calcite precipitation and dolomite precipitation).